Optimizing Student Career Planning Through Training and Evaluation of Teacher Guidance and Counseling Service Programs in SMKN 1 Pancur Batu - Nufus Adlina, Cut Raisyah; Lesmana, Gusman (Jurnal Riset Ilmu Pendidikan, 2023)
Vocational High School is a form of upper secondary education which aims to produce workers who are ready to work in the industrial sector. This can be seen from the fact that Vocational High School graduates are prepared with skills and experience through implementing Field Work Practices (PKL) during class XI or XII. It is hoped that these skills and experiences will become capital for graduates when entering the world of work after graduating. However, it was found that many vocational school graduates face difficulties in determining their career direction and goals. Therefore, community service activities are carried out to provide guidance to class XI and class XII students at SMKN 1 Pancur Batu so that they are ready to continue their careers after graduating. One of the efforts made is to provide an understanding of the importance of continuing education to tertiary level. The results of this service activity show that participants have begun to realize how important higher education is in supporting their career preparation